2020
DOI: 10.1139/cjp-2020-0039
|View full text |Cite
|
Sign up to set email alerts
|

Non-relativistic eigensolutions of molecular and heavy quarkonia interacting potentials via the Nikiforov Uvarov method

Abstract: In this paper, we obtained the analytical eigensolutions of the radial Schrodinger equation using the Nikiforov Uvarov method. Special cases of the modeled potential were discussed. We obtained the energy eigenvalues expressions for both quarkonia and diatomic molecular interacting systems. In particular, we computed the masses of charmonium and bottomonium mesons. The pure vibrational energy levels, inertia rotational constant and the first two centrifugal distortion constants of the Kratzer-Fues oscillator w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…(28) and (29) into (27), we obtained the expression (30) Finally, using the respective notations and given in Eqs. (17)(18)(19), we obtained the energy eigenvalue expression for the KPIQP as (31)…”
Section: Solution Of the Radial Schrodinger Equationmentioning
confidence: 99%
“…(28) and (29) into (27), we obtained the expression (30) Finally, using the respective notations and given in Eqs. (17)(18)(19), we obtained the energy eigenvalue expression for the KPIQP as (31)…”
Section: Solution Of the Radial Schrodinger Equationmentioning
confidence: 99%
“…There are several studies with the Cornell potential in literature. For instance, Flores [9,30] studied the Schrödinger equation with the Cornell potential using variational method and supersymmetric quantum mechanics [9,10,[30][31][32]. Bruni et al [8] calculated the energy configuration for a quark-antiquark pair from the Nambu-Goto action.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that this configuration energy has the shape of a Cornell potential [8]. Khoka et al [31,33] utilized the analytical exact iterative method to solve N-dimensional Schrödinger equation with an extended Cornell potential [31]. They found the energy and mass spectrum of heavy quarkonia [31].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations